Currency Risk and Local Intertemporal Asset Pricing Model. Case of Russia - Илья Игоревич Кучин (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2016)
Ilya I. Kuchin - HSE.E-mail: ikuchin@hse.ruThe research is concentrated on the issue of evaluating the risk factors impact on the Russian market asset pricing. John Campbell developed a global intertemporal asset pricing model that takes into account a number of risk factors in 2013. Emerging markets, including Russia, each possesses unique traits that make using global model risk factors in the local model complicated. Extra risks that are connected with developing countries market inefficiency, limited diversification possibilities, structural and institutional aspects command different key asset pricing influence factors and application of local models that estimate the demanded profitability per own capita. In particular, key interconnected Russian market indexes of the currency rate and oil pricing were chosen as risk factors for the Russian market. The model was tested using data on 102 non-financial Russian companies’ during 2005–2013. The novelty in this study was as follows: first, the new model of assessment of foreign exchange risk factors influence the cost of equity capital; secondly, made allowance for the influence of the exchange rate risk on cash flow fluctuations in the discount rate and idiosyncratic volatility in intertemporal asset pricing models; and thirdly, the tests carried out intertemporal asset pricing models in the Russian market. The results confirmed a strong model specification that talks about the possibility of its use and need to consider macro factors in the formation of the investment portfolio for the long term.